GC-MS ANALYSIS OF INVASIVE AQUATIC WEED, PISTIA STRATIOTES L. AND EICHHORNIA CRASSIPES (MART.) SOLMS - Tyagi, Tulika; Agarwal, Mala (International Journal of Current Pharmaceutical Research, 2017)
Objective: To investigate the bioactive components of an invasive aquatic weed, Pistia stratiotes L. and Eichhornia crassipes (Mart.) Solms vegetative parts by using Gas Chromatography-Mass Spectrometer (GC-MS). Methods: The chemical compositions of the ethanol extract of whole plant Pistia stratiotes L. and Eichhornia crassipes (Mart.) Solms was investigated using Agilent Technologies GC-MS (GC-7890A, MS 5975C). Results: The results of GC-MS analysis of the ethanolic extract revealed the existence of 28 phytochemical compounds in Pistia stratiotes L. n-Hexadecanoic acid,-11-Hexadecenoic acid, ethyl ester, Hexadecanoic acid, ethyl ester, Octadecanoic acid, ethyl ester, 2-Cyclopenten-1-one, 5-hydroxy-2,3-dimethyl, L-Glutamine, 2-Pentadecanone, 6,10,14-trimethyl, Linolelaidic acid, methyl ester, 9,12,15-Octadecatrienoic acid, methyl ester,(Z,Z,Z), Nonadecane, 12,15-Octadecadiynoic acid, methyl ester, Hexadecanoic acid, 2-hydroxy-1-(hydroxymethyl)ethyl ester, Diisooctyl phthalate, Docosanoic acid, ethyl ester, Stigmasterol, Bis(2-ethylhexyl) phthalate, 1-Monolinoleoylglycerol trimethylsilyl ether, Ethyl iso-allocholate are the major compound. The ethanolic extract of Eichhornia crassipes (Mart.) Solms contains 43 phytochemical compounds of high and low molecular weight n-Hexadecanoic acid, E-11-Hexadecenoic acid, ethyl ester, Palmitic acid, Phytol, 9,12,15-Octadecatrienal, 9,12-Octadecadienoic acid, ethyl ester, Linolenic acid, ethyl ester, Stearic acid, ethyl ester, Hexadecanoic acid, 2-hydroxy-1-(hydroxymethyl)ethyl ester, Î±-Glyceryl linolenate, 1-Monolinoleoylglycerol trimethylsilyl ether, Linoleic acid, 2,3-bis-(O-TMS)-propyl ester, Stigmasterol, Linolelaidic acid, methyl ester, 9,12,15-Octadecatrienoic acid, ethyl ester, (Z,Z,Z), Ethyl iso-allocholate, Cholesta-22,24-dien-5-ol, 4,4-dimethyl are the major compounds. These results indicates Pistia stratiotes L. and Eichhornia crassipes (Mart.) Solms possess potent antioxidant, anti-inflammatory, anticancer, antitumour, antiarthritic, cancer preventive, antibacterial effects so can be recommended as a plant of phytopharmaceutical importance. Conclusion: The ethanol extract of Pistia stratiotes L. and Eichhornia crassipes (Mart.) Solms proves as a potential source of bioactive compounds of pharmacological importance.